Implementasi Pembelajaran Tematik Berbasis Sistem dalam Jaringan di Kelas II Sekolah Dasar Negeri Karangmangu 02 - Sairah, Sairah (Universitas Sebelas Maret, 2020)
This research aims to describe implementation of system-based thematic learning, in terms of supporting and inhibiting factors, efforts to optimize supporting factors, and overcoming inhibiting factors. This research was conducted at thrid grade SDN Karangmangu 02 Kab Tegal. This research used descriptive qualitative methods. The subjects of this research were teachers, students, and parents. Data collection techniques were observation, interviews, and document study. Implementation of online system-based thematic learning to regard condition of students and parents considerations. In implementation there are supporting factors are interest in learning, maximum parental assistance, availability of mobile phones, internet quota, and a stable network. While the inhibiting factors are lazy to learn, less maximal parental assistance, limited cellphone facilities, internet quota limited, and unstable network. Efforts to optimize the supporting factors are motivation and data collection on the distribution of internet quota assistance on a regular basis. Efforts to overcome inhibiting factors are teacher motivation and assistance, between parents and students, as well as the role of the community. This research is important for improve learning during the Covid-19 pandemic.